1993
DOI: 10.1007/bf00203106
|View full text |Cite
|
Sign up to set email alerts
|

Cu 2p absorption spectroscopy as a probe for the site occupancy of (ZnxCu1−x)WO4 solid solution

Abstract: Abstract. The solid solution sanmartinite (ZnWO4) cuproscheelite (CuWO4) has been studied using Cu 2p X-ray absorption spectroscopy. While a single L3 absorption peak is observed for CuWO4, two distinct L 3 absorption peaks with a separation of ~0.8 eV are observed for the intermediate samples in the solid solution. The two peaks represent distinct Cu sites: one with all CuO6 next nearest neighbours in the (Cu,Zn)O 6 chains, another having at least one ZnO 6 next nearest neighbout. Both sites show a linear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Therefore, when subjected to extreme pressure environments, the researchers [40][41][42][43] have reported that these crystals have a monoclinic structure characterized by space group (P2/c), point group symmetry (C 4 2h ) and two molecular formula units per unit cell (Z = 2) [43,44]. On the other hand, under low-pressure conditions at room temperature, these crystals exhibit a triclinic structure with space group (P 1), point group symmetry (C i ) and two molecular formula units per unit cell (Z = 2) [45][46][47]. Moreover, CuWO 4 crystals with triclinic structure are influenced by Jahn-Teller effect due to the presence of Cu 2+ ions, which promote distortions on octahedral [CuO 6 ] clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when subjected to extreme pressure environments, the researchers [40][41][42][43] have reported that these crystals have a monoclinic structure characterized by space group (P2/c), point group symmetry (C 4 2h ) and two molecular formula units per unit cell (Z = 2) [43,44]. On the other hand, under low-pressure conditions at room temperature, these crystals exhibit a triclinic structure with space group (P 1), point group symmetry (C i ) and two molecular formula units per unit cell (Z = 2) [45][46][47]. Moreover, CuWO 4 crystals with triclinic structure are influenced by Jahn-Teller effect due to the presence of Cu 2+ ions, which promote distortions on octahedral [CuO 6 ] clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as may be expected from crystal chemistry, it follows that in all the samples Cu 2+ is located in more than one site. Such additional features have been used previously to model site occupancies ifi (ZnxCUl_x)WO 4 (Schofield et al, 1993), but are not sufficiently detectable for such analysis here. If these features are indeed due to multiple site occupancies, then the different energy and shape of the L3 peaks for BM 1964,702 andBM 1983,97 from that of BM 1937,1355 may be assigned to an extra absorption component representing the existence of an extra Cu 2+ site.…”
Section: Resultsmentioning
confidence: 99%
“…Tungstates have technologically important applications as scintillators [1], laser host materials [2], photocatalysts [3], and heterogeneous catalysts [4]. Many properties of tungstates can be further controlled by doping or by making solid solutions with other tungstates [5,6,7,8,9,10]. The doping approach is of particular interest because of a wide range of possible chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Both ZnWO 4 and NiWO 4 crystallize in the wolframite structure (space group P 2/c) with two formula units per unit cell [11,12] ] octahedra. However, multiple articles showed that on a microscopic level the local structure in these (or similar) materials can be quite complex [5,10]. The formation of solid solutions also changes the environment around B cations and increases the unit cell volume in proportion to A concentration (for Zn c Ni 1 -c WO 4 , see [13,14,15]; the ionic radii are 0.72 Å and 0.69 Å for Zn and Ni, respectively [16]).…”
Section: Introductionmentioning
confidence: 99%